Resilience to Alzheimer's disease associates with alterations in perineuronal nets - Vries, Luuk E.; Bahnerth, Anouck; Swaab, Dick F.; Verhaagen, Joost; Carulli, Daniela (Alzheimer's & dementia, 2025)
INTRODUCTION Some individuals show intact cognition despite the presence of neuropathological hallmarks of Alzheimer's disease (AD). The plasticity of parvalbumin (PV)‐containing interneurons might contribute to resilience. Perineuronal nets (PNNs), that is, extracellular matrix structures around neurons, modulate PV neuron function. We hypothesize that PNNs play a role in resilience to AD. METHODS PNN amount and morphology were determined in immunolabelled sections of the frontal cortex of control, AD and resilient subjects. Expression levels of genes related to PNNs and microglia signatures were evaluated by bulk RNA sequencing. RESULTS The expression of the PNN‐component aggrecan around PV neurons is decreased in resilient and AD subjects, whereas PNN‐sugar chains are reduced only in resilient subjects. In AD, fewer presynaptic terminals on PV neurons are detected and genes related to PNN degradation are upregulated. DISCUSSION These data show distinct PNN changes in individuals resilient to AD, which may contribute to preserved cognition despite the neuropathology. Highlights Aggrecan levels are decreased in the frontal cortex of AD and resilient subjects. In resilient subjects, WFA+ PNNs are reduced around neuronal somata. In AD patients, PV neurons show disrupted WFA peridendritic staining and synaptic loss. Expression levels of PNN‐degrading enzymes are higher in AD. Excitatory neurons bearing a PNN show low amounts of ptau.